Reperfusion Strategy of ST-Elevation Myocardial Infarction: A Meta-Analysis of Primary Percutaneous Coronary Intervention and Pharmaco-Invasive Therapy - Li, Kaiyin; Zhang, Bin; Zheng, Bo; Zhang, Yan; Huo, Yong (Frontiers in Cardiovascular Medicine, 2022)
Background Pharmaco-invasive therapy (PIT), combining thrombolysis and percutaneous coronary intervention, was a potential complement for primary percutaneous coronary intervention (pPCI), while bleeding risk was still a concern. Objectives This study aims to compare the efficacy and safety outcomes of PIT and pPCI. Methods A systematic search for randomized controlled trials (RCTs) and observational studies were conducted on Pubmed, Embase, Cochrane library, and Scopus. RCTs and observational studies were all collected and respectively analyzed, and combined pooled analysis was also presented. The primary efficacy outcome was short-term all-cause mortality within 30 days, including in-hospital period. The primary safety outcome was 30-day trial-defined major bleeding events. Results A total of 26,597 patients from 5 RCTs and 12 observational studies were included. There was no significant difference in short-term mortality [RCTs: risk ratio (RR): 1.14, 95% CI: 0.67–1.93, I2 = 0%, p = 0.64; combined results: odds ratio (OR): 1.09, 95% CI: 0.93–1.29, I2 = 0%, p = 0.30] and 30-day major bleeding events (RCTs: RR: 0.44, 95% CI: 0.07–2.93, I2 = 0%, p = 0.39; combined results: OR: 1.01, 95% CI: 0.53–1.92, I2 = 0%, p = 0.98). However, pPCI reduced risk of in-hospital major bleeding events, stroke and intracranial bleeding, but increased risk of in-hospital heart failure and 30-day heart failure in combined analysis of RCTs and observational studies, despite no significant difference in analysis of RCTs. Conclusion Pharmaco-invasive therapy could be an important complement for pPCI in real-world clinical practice under specific conditions, but studies aiming at optimizing thrombolysis and its combination of mandatory coronary angiography are also warranted.